Implementation of an active mass damper to control vibrations in a Lively footbridge - Carlos Moutinho (2007)
This paper describes the work involving a real implementation of an active control system to reduce vibrations in a lively footbridge located at FEUP. This structure has some natural frequencies around 2Hz which can be easily excited by some pedestrian activities. Although the levels of vibration may not be considered excessive according to some design codes, this footbridge experiments regularly unusual vibrations for this type of structure, which has motivated the implementation of a control system for research purposes. The active control developed is composed by an Active Mass Damper commanded by a controller based on the Velocity Feedback Control law. The efficiency of this control system is evaluated in terms of the reduction of the response when the structure is excited by several pedestrian loads.